2022
DOI: 10.1097/hcr.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response to Exercise and Recovery

Abstract: Attenuated chronotropic index and heart rate recovery, documented during treadmill exercise testing in 13,887 patients without known cardiovascular disease, were both associated with worse cardiovascular outcomes and mortality. Their predictive value was independent of cardiorespiratory fitness, and was more pronounced when the two abnormal heart rate measures coexisted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In addition, exercise-induced accumulation of muscle metabolites and uncontrolled thermoregulation can mediate cardiac sympathetic nerve activity disturbances, ultimately leading to HRR abnormalities (13, 21). However, a recent study found that the predictive value of HRR2 was independent of METs (9), which is consistent with our findings. Therefore, it is more reasonable to explore the optimal time point for HRR to predict endpoint events, considering the study protocol, population, and other conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, exercise-induced accumulation of muscle metabolites and uncontrolled thermoregulation can mediate cardiac sympathetic nerve activity disturbances, ultimately leading to HRR abnormalities (13, 21). However, a recent study found that the predictive value of HRR2 was independent of METs (9), which is consistent with our findings. Therefore, it is more reasonable to explore the optimal time point for HRR to predict endpoint events, considering the study protocol, population, and other conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Heart rate recovery (HRR) represents the balance between parasympathetic reactivation and sympathetic regression based on exercise stress testing (ET) (4,5). The correlation between aberrant HRR and the incidence of MACE in individuals with suspected CAD has been supported by several research (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…It is common to observe changes in the central nervous system, such as chronotropic incompetence (CI) and a slower heart rate recovery after exercise [3,4]. Since the autonomic nervous system plays a crucial role in heart rate (HR) recovery after exercise, a delay in this response may indicate autonomic dysfunction, which can be a predictor of disease development and progression [5]. CI has multifactorial origins, but adopting an active lifestyle has been suggested as a safe and effective approach to prevent or reduce changes in insulin and cardiac autonomic neuropathy in individuals with T2DM [6-8], resulting in signi cant improvements in quality of life.…”
Section: Introductionmentioning
confidence: 99%